How Much Do Perceptions of Corruption Really Tell Us? - Claudio Weber Abramo (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
Regressions and tests performed on data from Transparency International Global Corruption Barometer (GCB) 2004 survey show that personal or household experience of bribery is not a good predictor of perceptions held about corruption among the general population. In contrast, perceptions about the effects of corruption correlate consistently among themselves. However, no consistent relationship between opinions about general effects and the assessments of the extent with which corruption affects the institutions where presumably corruption is materialized is found. Countries are sharply divided between those above and below the US 10,000 GDP per capita line in the relationships between variables concerning corruption. Among richer countries, opinions about institutions explain very well opinions concerning certain effects of corruption, while among poorer countries the explanatory power of institutions for the effects of corruption falls. Furthermore, tests for dependence applied between the variables in the sets of respondents for each of 60 countries also show that, for most of them, it is likely that experience does not explain perceptions. On the other hand, opinions tend to closely follow the trend of other opinions. Additionally, it is found that in the GCB opinions about general effects of corruption are strongly correlated with opinions about other issues. The correlation is so strong as to justify the hypothesis that it would suffice to measure the average opinion of the general public about human rights, violence etc. to accurately infer what would be the average opinion about least petty and grand corruption. The findings reported here challenge the value of perceptions of corruption as indications of the actual incidence of the phenomenon.
Keywords: D73; H11; K42; 330; Corruption; perceptions; corruption indicators; Korruption; Messung; Öffentliche Meinung; Wirtschaftsindikator; Schätzung; Welt